Thermo-Electro Chemical Surface Energy Conversion Influence on Air Pollution - Sevaljevic, Mirjana Miladin; Ionel, Ioana; Pavlovic, Milan; Vetres, Ion (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Water vapor condensation and crystallization active centers on gas exposed solid dust particle enable thermo-electrochemical energy catalytic storage and conversion. Thermodynamic diagnostic method is developed for determination of catalyst working function and thermo-electro chemical surface reaction kinetic. The diagnostic results of catalyst working function and hydrogen evolution rate constants justify the functional dependence obtained on the basis of monitoring data in six day period, in different seasons and location in Romania and Serbia These indicate to relative electric permittivity dominant influence, depending on Helmholtz surface and Helmholtz outer and diffusion planes in catalyst electric double layer.